Evaluating Sukuk Default Factors: A Case Study on Dana Gas Sukuk in the UAE - Ali, Mohammed Imad; Hasan, Aznan; Sharofiddin, Ashurov (Journal of Islamic Finance, 2022)
In the last couple of years, the Islamic finance industry was rocked by several sukuk defaults, the most prominent among them being Dana Gas Sukuk. These defaults led to hordes of questions related to Shariah governance, unstandardized legal documentation, Shariah non-compliant structure, lack of intent and transparency, incongruence in governing laws, and a lack of regulatory support. This paper assesses Dana Gas Sukuk by conducting a qualitative analysis to determine the circumstances that led to the failures of this sukuk. Using secondary sources this paper employs a content analysis method and scrutinizes the sukuk understudy with a special focus on its structure, governance mechanism, and legal jurisdiction. Thus, the study suggests standardizing the legal documentation and Shariah interpretation of the Islamic capital market, as it would reduce the risk of Shariah non-compliance and remove all the uncertainty and ambiguities and would help to avoid such sukuk default. Finally, it can be asserted that an attempt is made to offer some recommendations that hopefully will avert similar defaults in the future and help the Islamic finance industry to achieve greater standardization and clarity.